Determination of the Host Range of Tree and Herb Rhizobia for their Alternative Legumes - Meghvansi1,2, S.K. Mahna1, Syed Farook Ali1*, L.S. Rawat1, M.K. (Journal of Phytology, 2010)
A series of experiments were conducted in the green house and in growth chamber to test the rhizobia of Leucaena leucocephala (Lam) de Wit, Sesbania sesban (L) Merr. Tephrosia purpurea (L) Pers. and Crotalaria medicaginea (Lam) to determine their host range in other tree and herb legumes as alternative host. Other tree legumes under this study included Albezzia lebbeck (L.) Benth., Prosopis juliflora (Sw.) DC, Acacia nilotica (L.) Willd, Acacia senegal (L.) Willd, Acacia leucophloea and herb legumes included Vigna radiata (L.) R. Wilczek, Vigna mungo (L.) Hepper, Dolichos lablab (L.) Sweet, Pisum sativum (L.) and Indigofera tinctoria (L.). Promiscuity of L. leucocephala was observed for both tree and herb rhizobia but S. sesban and T. purpuria were very specific in their rhizobial requirement and could be nodulated only by their own rhizobia. However, Acacia spp. were not found be nodulated by any of the studied isolates. Ineffective nodules have been observed in D. lablab. The cross infection of agriculturally important legumes with isolates from wild legumes may prove a useful mean of increasing nitrogen contents within these plants. Key words: Host range, Rhizobia, Nodulation, Legumes <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Syed Farook Ali et al. Determination of the Host Range of Tree and Herb Rhizobia for their Alternative Legumes. J Phytol 2/7 (2010) 101-106.